Addendum to "Recent Publications," Locke Studies 20 (2020): Japanese Language Publications - Numao, J. Kei (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2021)
This is an addendum to the 2020 bibliographic article "Recent Publications," Locke Studies 20 (2020): 1-16. It contains 14 items of interest to Lockeans published in Japanese between 2018-2020 and not yet included in the John Locke Bibliography.